Development of hesperidin solid dispersion for improved solubility and dissolution using mannitol and PVP K30 as carriers - Swarup, Pallavi; Agrawal, Gopal Prasad (Creative Pharma Assent, 2024)
Background: Despite its six-hour half-life, Hesperidin, a bioflavonoid with therapeutic benefits, has low water solubility and bioavailability. This limits treatment. This study improved hesperidin solubility and dissolution by making solid dispersions using appropriate carriers. Methodology: Solid dispersions of hesperidin were prepared using two methods: kneading and solvent evaporation. The carriers utilized in the study were polyvinylpyrrolidone K30 (PVP K30) and mannitol. The formulations were evaluated based on various parameters, including yield, solubility, dissolution rate, drug content, and structural analysis using techniques such as X-ray diffraction (XRD), differential scanning calorimetry (DSC), and infrared (IR) spectroscopy. Results: Solid dispersions yielded 81.2% to 97.5% by weight and included 93.7% to 98.4% drug content. Hesperidin's solubility increased 3.72- to 24.05-fold, with a maximum drug release of 64.06% within 30 minutes. Comparatively, formulations with mannitol as the carrier demonstrated higher solubility (24.05 times) and dissolution (54.06%) than those containing PVP K30 (20.16 times and 34.36%). Discussion: Different carriers alter hesperidin solubility and dissolution. Mannitol improved drug release more than PVP K30. XRD and DSC experiments showed hesperidin's crystalline character changed in solid dispersions, possibly explaining its improved dissolving. IR spectroscopy showed physical dispersion because medication and carriers did not interact chemically. Conclusion: The study showed that solid dispersing hesperidin improves its solubility and dissolution. Drug release was greater with mannitol than with PVP K30. Solid dispersion formulations may improve the bioavailability of poorly soluble medicines like hesperidin.